Implementasi Sikap Bela Negara Guna Mewujudkan Ketahanan Pribadi (Studi di KB-TKIT Bintang Qur’an di Boyolali) - Halimah Rachmadany (Universitas Gadjah Mada, 2021)
ABSTRACT The success of state defense education at an early age is crucial for the formation of personal resilience.Problems that appear (1) how is the implementation of state defense education for early childhood in kindergarten?;(2) what are the factors that support and hinder the educational process of defending the state in kindergarten?;dan (3) what is the effectiveness of state defense education to realize personal resilience?. The location of theresearch was carried out at TKIT Bintang Qur’an Boyolali using descriptive qualitative research methods withHuberman analysis techniques. The results showed that the implementation of state defense education for childernaged 5-6 years at TKIT Bintang Qur’an has been running systematically and realistically in accordance with theinstitution’s goals, namely to create a generation that faithful, pious, has noble character, has good character andhas personal resilience. In the implementation of state defense education, there are supporting and inhibiting factors,child development abilities, environment, facilities and infrastucture, exemplary attitudes of educators as well ascollaboration programs with parents and the learning strategies used. The effectiveness of state defense educationcan be seen from the characteer of the students at TKIT Bintang Qur’an who have a sense of love for the homelandas evidences by implementing behavior in accordanc with Pancasila, childern are able to sing national and regionalsongs, like various cultures that exist in Indonesia. Has empathy and tolerance, is accustomed to doing activitiescooperatively and mutual cooperation, has self confidence and the spirit of a leade